2014
DOI: 10.1162/adev_a_00031
|View full text |Cite|
|
Sign up to set email alerts
|

Wage Differentials between Foreign Multinationals and Local Plants and Worker Quality in Malaysian Manufacturing

Abstract: Using industrial census data for 2000, and smaller sets of survey data for 2001–2004, this paper examines the extent of wage differentials between medium-large (20 or more workers) foreign multinational enterprises (MNEs) and local plants in Malaysia's manufacturing industries. On average, wages in sample MNEs were higher than in local plants by two-fifths or more. In addition to being more capital-intensive and relatively large, MNEs also hired higher shares of workers in highly paid occupations and with mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In addition, similar evidence for Malaysian plants in [2000][2001][2002][2003][2004] (Ramstetter 2013) also suggests the existence of positive, MNE-local wage differentials after accounting for both worker education and occupation, in addition to other plant characteristics, both when all industries are combined and at the industry level. However, none of these studies account for the potentially important effect of a plant's export status on MNE-local wage differentials.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, similar evidence for Malaysian plants in [2000][2001][2002][2003][2004] (Ramstetter 2013) also suggests the existence of positive, MNE-local wage differentials after accounting for both worker education and occupation, in addition to other plant characteristics, both when all industries are combined and at the industry level. However, none of these studies account for the potentially important effect of a plant's export status on MNE-local wage differentials.…”
Section: Introductionmentioning
confidence: 75%
“…As described in the introduction, when large samples of all manufacturing plants are used, previous studies have found that MNEs paid significantly higher wages than local, private plants in Indonesia in 1996(Lipsey and Sjöholm 2004aRamstetter and Narjoko 2013) and local (private and state-owned) plants in Malaysia in [2000][2001][2002][2003][2004] (Ramstetter 2012a(Ramstetter , 2013. These studies are distinguished from other studies of MNE-wage differentials by the important fact that they account for the educational background and sex of a plant's workers, in addition to plant size, and a plant's capital intensity or a proxy.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Precision machining is an important part of the foundation of modern high-tech technology. With the rapid development of science and technology, precision processing technology as the basis of high-tech development also has a growing, processing precision, processing efficiency in soon, in the future, precision machining technology is to a higher precision, higher efficiency, largescale and miniaturization direction (Obashi et al, 2016) (Ramstetter et al, 2014) (Ando et al, 2014).…”
Section: Research On the Core Technology And The Development Tendencymentioning
confidence: 99%